Effects of addition of Aspergillus oryzae culture and 2‐hydroxyl‐4‐(methylthio) butanoic acid on milk performance and rumen fermentation of dairy cows. (10th August 2016) - Sun, Hua; Wu, Yueming; Wang, Yanming; Wang, Chong; Liu, Jianxin
Abstract: To investigate effects of Aspergillus oryzae culture (AOC) and 2‐hydroxy‐4‐(methylthio) butanoic acid (HMB) on milk performance and rumen fermentation of dairy cows. Sixty‐four multiparous Chinese Holstein cows were randomly allocated into four experimental diets: (i) Control diet; (ii) AOC diet: 5 g AOC/day per head; (iii) HMB diet: 25 g HMB/day; and (iv) AH diet: 5 g AOC plus 25 g HMB/day. Added HMB tended to increase the yield of milk protein ( P = 0.06) and 3.5% fat‐corrected milk ( P = 0.08) and milk fat content ( P = 0.09). Milk fat yield ( P = 0.03) and the contents of milk protein ( P = 0.05) were increased by adding HMB. The cows fed on AOC diet had a tendency for higher body weight (BW) gain ( P = 0.08). Addition of AOC, HMB and AH increased content of microbial protein (MCP) and total volatile fatty acids (VFA) ( P < 0.01) in rumen fluid. Populations of rumen fungi, Fibrobacter succinogenes and Ruminococcus flavefaciens relative to total bacterial 16S rDNA ( P ≤ 0.03) and activity of carboxymethylcellulase (CMCase) ( P < 0.01) were increased with added AOC or HMB. It is inferred that added AOC or HMB can increase the contents of MCP and total VFA potentially by stimulating rumen microbe populations and CMCase activity.